(untitled) (Research, Society and Development, 2020)
The high resistance to antimicrobials has made hospitals a potentially dangerous environment for the development of HAIs, especially when associated with multi-resistant bacteria such as A. baumannii. The work aimed to evaluate the incidence of multidrug-resistant Acinetobacter baumannii described in the literature through a meta-analysis. A meta-analysis of a qualitative and quantitative nature was carried out in which original articles and review articles that presented data on the occurrence and existence of multidrug resistance in Acinetobacter baumannii were evaluated. The Scientific Electronic Library on Line (SciELO) and Medical Literature Analysis and Retrieval System Online (Pubmed / MEDLINE) databases were consulted using the descriptors "Acinetobacter baumannii," "multi-resistance," "IRAS," "incidence." Most studies were carried out in 2018. In general, most studies were cross-sectional 85.00% (n = 17) and cohort 15.00% (n = 3). In the selected studies, 5877 cases were reported, of which 3544 corresponded to multi-resistant species of Acinetobacter. The cumulative prevalence ratio corresponded to 0.603 with a 95% confidence interval [0.590 to 0.615]. The analysis of the temporal trend of the Ratio of the prevalence of multidrug-resistant Acinetobacter baumanni according to the year of the selected studies indicated that the PR suffered a decline in 2009 and 2013 and a new tendency to increase from 2015 and suffered small fluctuations until 2019, the trend did not show significant (R2 = 0.0772). Therefore, the MDR profile is worrying, given the currently available therapeutic alternatives.